Os mapas das pedras brilhantes: a cartografia dos sertanistas, dos engenheiros militares e dos padres matemáticos sobre o Distrito Diamantino do Serro do Frio (1714-1771) - Carmem Marques Rodrigues (2014)
Mines rich in diamonds were official discovery in 1729 in the backlands of the Serro Frio. Then the Portuguese crown began to organize their actions in the backcountry, with the goal of streamlining the administration of mining. In this context, the maps have become essential tools, built according to the military academies methods and following the graphic conventions systematized throughout the eighteenth century. These maps were essential tools for the politics for diamonds. Even before the official discovery of the stones, the hinterlands of Serro Frio were also the principal object of the explorer's scripts and maps. These representations had a pragmatic and/or political nature. Practically, roadmaps were descriptions of roads, rivers, creeks and streams of the Serro Frio that led to gold and diamonds, or also bring clues to the way of Esmeraldas Mountains. In a political way, were a feature used by explorers to request favors and realize their discoveries actions. These two ways of representing the Serro Frio - the official and the explorers - although apparently unconnected, maintained an intensive dialogue, providing the exchange of cartographic methods, which led to certain entities geographical to persist or disappear throughout the history of the Diamond District.